Exploring youth migration and the food security nexus: Zimbabwean youths in Cape Town, South Africa (African Human Mobility Review, 2021)
In recent times, debates on the connection between migration and development surfaced as essential discourses in contemporary development issues. Consequently, this led to the birth of what is currently popularly coined as the migration-development nexus. In addition, there has been an evolution of the food security topic in various developmental discussions. Nevertheless, little attention has been given to the relationship between international migration and food security in the context of development in the global south. Moreover, missing in the literature is the conversation on migration and food security with particular attention to youths who constitute a vulnerable yet economically active group. Furthermore, there has been an ongoing engaging debate on the impact of remittances, whether remittances for household use are developmental in nature or not. This study, in contributing to the above debates, explores the link between youth migration and food security, and is based on a quantitative empirical study on Zimbabwean migrant youths in Cape Town, South Africa. The research presents comprehensive perspectives on the complexities linked to the reasons for youth migration in connection to food security, the importance of remittances on food security in the place of origin and levels of food insecurity in the place of destination. Results from this study can provide useful data for various stakeholders involved in both international migration and food security development agendas.